Executives' compensation policy: a study on Brazilian, North American and British industrial companies (Gestão & Regionalidade, 2015)
The aim of this study is to verify how the executives' compensation policy, in the level and structure perspectives, according to the proposition of Murphy (1999), has been practiced by Brazilian, North American and British industrial companies, in the period from 2007 to 2010. Data collection was documentary and the sample consisted of 400 industrial companies, being 30 Brazilian, 47 British and 323 North American. The results show that North American executives' compensation, regarding the level, is almost three times higher than Brazilian and English executives. As for the compensation structure, also was not found similarities in the compensation policy for Brazilian, North American and British executives, and most of North American executives' compensation is based on stock market shares. It is concluded that the executives' compensation policy practiced by Brazilian, North American and British industrial companies, in the period from 2007 to 2010 shows no similarities in the perspectives of level and structure.